Concurrence of Crossed Cerebellar Diaschisis and Parakinesia Brachialis Oscitans in a Patient with Hemorrhagic Stroke - Yung-Tsan Wu; Shin-Tsu Chang; Liang-Cheng Chen; Tsung-Ying Li (Case Reports in Medicine)
Crossed cerebellar diaschisis (CCD) is defined as a reduction in blood flow in the cerebellar hemisphere contralateral to the supratentorial focal lesion. The phenomenon termed parakinesia brachialis oscitans (PBO) in which stroke patients experience involuntary stretching of the hemiplegic arm during yawning is rarely reported. The concurrence of CCD and PBO has never been described. A 52-year-old man had putaminal hemorrhage and demonstrated no significant recovery in his left hemiplegia after intensive rehabilitation, but his gait improved gradually. Two months after the stroke, the single photon emission computed tomography (SPECT) showed CCD. Four months after the stroke, the patient noticed PBO. The follow-up SPECT showed persistent CCD and the patient’s arm was still plegic. The frequency and intensity of PBO have increased with time since the stroke. We speculate that the two phenomena CCD and PBO might share similar neuroanatomical pathways and be valuable for predicting clinical recovery after stroke.